STUDI KEMAMPUAN MOTORIK ANAK USIA 10 TAHUN PADA DATARAN RENDAH DAN DATARAN TINGGI DI KABUPATEN JEMBER - Arif Miftahul Riski; Usman Wahyudi; Dona Sandy Yudasmara (Cahaya Ilmu Bangsa Institute, 2024)
Every sport or physical education activity will go well if students have adequate motor skills, which are basicaly the foundation of all physical education disciplines. The purpose of this study was to compare the motor skills of 10 year old chiIdren from the highlands and lowlands of Jember Regency, and to identify differences in motor skills. Survey research with a comparative design complements this research. 103 students were used as research subjects. The test kits used measure various motor skills including speed, agility, coordination, and balance. The findings of this study indicate that lowland students and highland students have no differences in motor skills which include elements of speed, coordination, and agility. Both groups of students have advantages in their respective motor skills, except for the element of balance, where students from the highlands are better than students from the lowlands.